Ethics of immigration: the issue of convicted criminals - Fabre, C (Wiley, 2016)
In this paper, I explore and probe Joseph Carens’ remarks, in his recent book The Ethics of Immigration, on the immigration status of foreign convicted criminals who have served their sentence, and who wish either to immigrate into our country or who are already here. Carens rejects deportation when it is not called for by considerations of national security, and agrees that considerations of public order can justify barring convicted foreign criminals from entering the country. I broadly agree with his arguments against deportation: my remarks in this respect are clari catory and exploratory as much as anything else. But (I argue) both his argument for open borders and his scepticism with respect to radical cosmopolitanism are in tension with his claim that past criminal convictions can act as a bar to entry.